2017
DOI: 10.1136/bmjopen-2017-018364
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the predictors of photoprotection and UVR dose to the face in patients with XP: a protocol using observational mixed methods

Abstract: IntroductionXeroderma pigmentosum (XP) is a rare genetic condition caused by defective nucleotide excision repair and characterised by skin cancer, ocular and neurological involvement. Stringent ultraviolet protection is the only way to prevent skin cancer. Despite the risks, some patients’ photoprotection is poor, with a potentially devastating impact on their prognosis. The aim of this research is to identify disease-specific and psychosocial predictors of photoprotection behaviour and ultraviolet radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…This study is part of a mixed‐methods programme of research aimed at improving photoprotection practices in XP patients (Walburn et al ., ). The cross‐sectional survey was completed between May and December 2016 by 156 participants in the United Kingdom, France, Germany, and the United States.…”
Section: Methodsmentioning
confidence: 97%
“…This study is part of a mixed‐methods programme of research aimed at improving photoprotection practices in XP patients (Walburn et al ., ). The cross‐sectional survey was completed between May and December 2016 by 156 participants in the United Kingdom, France, Germany, and the United States.…”
Section: Methodsmentioning
confidence: 97%
“…Sixty six patients diagnosed with XP (approximately 65% of total XP population in the UK) were recruited from the national XP specialist service at Guy's & St Thomas' NHS Foundation Trust. All were recruited as part of a larger mixed‐methods study of photoprotection in people with XP . Individuals of any age were eligible to participate if they had a confirmed diagnosis of XP.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, only the 21 days matching the period where the UVR dosimeter was worn was used. Detailed information about the diary can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological models employed to understand adherence, such as the Common-Sense Model of illness (Leventhal, Meyer, & Nerenz, 1980) and the Health Action Process Approach (Schwarzer, 2008), acknowledge the importance of social influence but the processes involved have not been examined. As part of a programme of mixed-methods research to improve adherence to photoprotection amongst people with Xeroderma Pigmentosum (XP; see Walburn et al, 2017), a very rare genetic condition, we identified gaps in the understanding of the influence of social processes on adherence. As part of a programme of mixed-methods research to improve adherence to photoprotection amongst people with Xeroderma Pigmentosum (XP; see Walburn et al, 2017), a very rare genetic condition, we identified gaps in the understanding of the influence of social processes on adherence.…”
Section: Statement Of Contributionmentioning
confidence: 99%